Economic Challenges of Labour Mobility within the EU - Kobelia, Zoriana (International Journal of Economics and Financial Issues, 2024)
The study’s relevance lies in the demographic challenges currently facing the EU, namely population ageing and declining birth rates, against the backdrop of global labour mobility. This work examines the multifaceted nature of labour migration and addresses the critical need for balanced migration management and effective integration practices. The aim is to harness the economic benefits of migration while minimising potential negative impacts on both the local population and migrants. The research aims to uncover these complex dynamics by proposing measures to enhance integration strategies and improve the efficiency of migration policies in the EU. The study’s novelty and scientific value stem from its integrative approach to analysing the economic consequences of migration. It highlights the importance of comprehensive migration policies that consider migration processes’ economic, social, and cultural aspects. The application of systemic, structural-functional, comparative, and statistical analysis gained insights into the impact of migration on the labour market, demographic trends, and migrant integration. The results indicate that migration can help to address labour market deficits and stimulate economic growth. It is emphasised that targeted investments in integration programmes that account for the specificities of diff erent migrant groups are necessary. This study contributes to the scholarly and policy discussion on labour migration in the EU, providing a basis for developing more nuanced and compelling migration and integration policies.
Economic Challenges of Labour Mobility within the EU
Keywords: Labour Migration, European Union, Integration Policy, Labour Market, Demographic Challenges, Economic Regulation